2021
DOI: 10.1021/acs.macromol.1c01273
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Biobased Polyimides from Diaminotruxinic Acid with Unique Bending Angles

Abstract: Biobased diamines with unique bending angles, βand δ-type truxinic acids, were prepared from functionalized 4nitrocinnamic acid derivatives via solid-state photodimerization and further chemical modification. The obtained diamines were polymerized with tetracarboxylic acid dianhydrides to produce soluble polyimides via chemical imidization at a high efficiency. The obtained δ-type-based polyimides exhibited a high thermostability at 10% weight loss temperature of ∼415 °C and good solubility in organic solvents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…[22][23][24][25] Since the properties of PIs are highly dependent on the chemical structures of dianhydrides and diamines, improved synthesis methodology of monomers with unique structures continues to drive the development of high-performance PI materials. [26][27][28] Recent studies have shown that incorporating of aromatic linkers with unique bending angles (including triarylamine, triarylmethane, spirobisbenzoxazole, and cinnamoyl photodimer-based structures [29][30][31][32][33][34][35][36][37][38][39] ) is becoming an effective approach to produce PIs with twisted backbones, which can improve the transparency and insulating properties through the decrease of interchain packing and increase of free volume. 38,40 In order to achieve a facile synthesis of PI with favorable processability, good transparency high thermal stability and mechanical strength, a novel triarylmethane-based diamine (DA-TFVE) with cross-linkable trifluorovinyl-ether (TFVE) groups was designed and successfully synthesized in this work (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] Since the properties of PIs are highly dependent on the chemical structures of dianhydrides and diamines, improved synthesis methodology of monomers with unique structures continues to drive the development of high-performance PI materials. [26][27][28] Recent studies have shown that incorporating of aromatic linkers with unique bending angles (including triarylamine, triarylmethane, spirobisbenzoxazole, and cinnamoyl photodimer-based structures [29][30][31][32][33][34][35][36][37][38][39] ) is becoming an effective approach to produce PIs with twisted backbones, which can improve the transparency and insulating properties through the decrease of interchain packing and increase of free volume. 38,40 In order to achieve a facile synthesis of PI with favorable processability, good transparency high thermal stability and mechanical strength, a novel triarylmethane-based diamine (DA-TFVE) with cross-linkable trifluorovinyl-ether (TFVE) groups was designed and successfully synthesized in this work (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since the properties of PIs are highly dependent on the chemical structures of dianhydrides and diamines, improved synthesis methodology of monomers with unique structures continues to drive the development of high-performance PI materials. 26–28 Recent studies have shown that incorporating of aromatic linkers with unique bending angles (including triarylamine, triarylmethane, spirobisbenzoxazole, and cinnamoyl photodimer-based structures 29–39 ) is becoming an effective approach to produce PIs with twisted backbones, which can improve the transparency and insulating properties through the decrease of interchain packing and increase of free volume. 38,40…”
Section: Introductionmentioning
confidence: 99%
“…However, both thermosetting and thermoplastic PI are hard to decompose for their features, resulting in serious environmental pollution and resource waste. [2,4,5] Up to now, the researches on PI recycling mainly focus on thermoplastic PI. For example, thermoplastic PI is ground into powder and used as additive to improve the mechanical properties and frictional resistance of base material, but the value-added is low.…”
Section: Introductionmentioning
confidence: 99%
“…However, both thermosetting and thermoplastic PI are hard to decompose for their features, resulting in serious environmental pollution and resource waste. [ 2,4,5 ]…”
Section: Introductionmentioning
confidence: 99%
“…), bulky pendant moieties, and building asymmetrical or noncoplanar structures (kink, spiro and cardo). [5][6][7][8][9][10][11][12][13][14][15] Unfortunately, such structural manipulations rarely result in a satisfactory performance since the disturbing of self-chain alignment and loosening of the chain stacking of aromatic polyimides will inevitably lead to the loss of their inherent properties, including, a significant decrease of the packing density arising from -CF 3 in both diamines and dianhydrides, 16,17 an unacceptable glass transition temperature (T g ) (<350 °C, differential scanning calorimetry (DSC); <400 °C, dynamic mechanical analyses (DMA); see Table S1 †) due to bulky pendant moieties, 13,18 a decline in decomposition temperature (T d5 , 365-470 °C) due to the incorporation of alicyclic structures, 11,[19][20][21] unacceptable coefficients of thermal expansion (up to 83 ppm K −1 ) due to the destruction of linear and rigid structures (cycloaliphatic), 22 and a limited effect on color elimination caused by the introduction of large aromatic pendant groups. 23 Therefore, an optimal molecular design to balance the thermal and optical properties of CPIs remains the current primary goal.…”
Section: Introductionmentioning
confidence: 99%